Studi Kelayakan Dermaga Kapal Latih Menunjang Badan Layanan Umum (BLU) - Irwan Jaya; Sugiyono; Fahri Ihsan (Hengkara Majaya, 2021)
Abstrack One of the government's programs is to optimize the distribution of goods, on the other hand, the existence of the Karaeng Galesong Barombong pier has not been optimized for the public, be it for commercial ports or popular ports. For this reason, this study aims to determine the feasibility of the Karaeng Galesong Barombong Pier as a public vessel. The population for this research is all sailors who have worked on the ship, while the sample in this study is the crew of the training ship and the users of the training ship at the Karaeng Galesong pier, up to 50 respondents. The research was carried out through observations and questionnaires, then the data obtained was tabulated and then analyzed by means of a cross table through a simple regression test. The results showed that the operation of the Karaeng Galesong pier by other parties would be 100% if it was supported by data availability, hence warehouse availability, meanwhile up to 80% if supported by a field availability as a place for loading / unloading of goods and only 20% will continue to operate the Karaeng Galesong pier elsewhere even though the loading and unloading field is not available. To be more optimal, it is expected that the competent parties will always update the data so that the Karaeng Galesong pier can be widely used by other parties.